2008
DOI: 10.1248/yakushi.128.1355
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Risk of Falling and Drugs in an Academic Hospital

Abstract: The purpose of this study was to investigate the frequency of inpatient falls and to evaluate the risk factors of drugs in an academic hospital. The study population consisted of inpatients at Ehime University Hospital in Japan and the study was conducted from April 1st to October 31st, 2006. Children and teenagers (<18 years old) were excluded. Inpatient falls were registered regularly with incident reports submitted by nurses and other hospital employees discovering the fall. Logistic regression techniques w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 25 publications
3
24
1
1
Order By: Relevance
“…We might have missed the association since these neurological conditions were underrepresented in our cohort of internal medicine inpatients. Chronic heart failure and the use of diuretics have been previously described as major fall risk factors in elderly patients [18][19][20][21][22], and were confirmed in our study cohort. Whether the causative mechanism for the association of heart insufficiency and the risk of falling is related to a malsupply of the brain, an impaired stability due to edema, or other consequences, is yet unclear.…”
Section: Discussionsupporting
confidence: 86%
“…We might have missed the association since these neurological conditions were underrepresented in our cohort of internal medicine inpatients. Chronic heart failure and the use of diuretics have been previously described as major fall risk factors in elderly patients [18][19][20][21][22], and were confirmed in our study cohort. Whether the causative mechanism for the association of heart insufficiency and the risk of falling is related to a malsupply of the brain, an impaired stability due to edema, or other consequences, is yet unclear.…”
Section: Discussionsupporting
confidence: 86%
“…Fifty seven percent of the studies did not specify the medication, class or substances included in the group (only mentioned, for instance, sedative hypnotics, without indicating any specific drug) (Costa-Dias et al, 2014;Pierce Jr. et al, 2013;Obayashi et al, 2013;Lamis et al, 2012;Chang et al, 2011;Bun, Serby, Friedmann, 2011;Mamun, Lim, 2009;Tanaka et al, 2008;Angalakuditi, Gomes, Coley, 2007;Vassalo et al, 2006;Krauss et al, 2005;Vassalo et al, 2004;Aisen, Deluca, Lawlor, 1992). Some articles focused their studies on all central nervous system medications (Lamis et al, 2012) (without establishing any distinction between the pharmacological groups).…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies attributed inpatient falls to anxiolytics use (Tapper, Risech-Neyman, Segupta, 2015;O'Neil et al, 2015;Mamun, Lim, 2009;Lamis et al, 2012;Frels, 2002;Dauphinot et al, 2014;Costa-Dias et al, 2014;Tanaka et al, 2008;Chang et al, 2011;Angalakuditi, Gomes, Coley, 2007;Shuto et al, 2010;Cashin, Yang, 2011;Vassalo et al, 2004;Mendelson, …”
Section: Anxiolyticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of that case-control study showed strong positive associations at 0 days for all classes of medication (β-blockers, angiotensin-converting enzyme inhibitors, calcium antagonists, thiazides). Surprisingly, only thiazides showed significant ORs of falling during elapsed times of [1][2][3][4][5][6][7][8][9][10][11][12][13][14] 16 A study showed that the current prescribing of angiotensin system-blocking medications, including angiotensin-converting enzyme inhibitors and angiotensinreceptor blockers, had a protective effect against fall risk in older people. 29 This prospective cohort study in 520 community-dwelling older people indicated that people taking angiotensin system-blocking medications were less likely to fall (OR 0.68, 95% CI 0.48-0.97; P,0.05) after adjusting for potential confounders.…”
mentioning
confidence: 99%